AKTIVITAS ANTIDIABETES KOMBINASI EKSTRAK TERPURIFIKASI HERBA SAMBILOTO (Andrographis paniculata (Burn.F.) NESS.) DAN METFORMIN PADA TIKUS DM TIPE 2 RESISTEN INSULIN - Eka Siswanto Syamsul; Agung Endro Nugroho; Suwijiyo Pramono (Majalah Obat Tradisional, 2011)
A. paniculata is a plant that can be used to overcome the disease diabetes. In DM there is a possibility of the use of therapy with oral hypoglycemic drugs, for example: metformin. This research was conducted using a complete random method indirectional pattern. This study aims to determine the potential of the combination of purified extract of sambiloto herbs and enhancement effects of metformin on blood glucose levels decrease in insulin resistant rats. Test animals used were divided 4 groups, group 1: metformin 45 mg / kg (positive control), group 2: purified extract of sambiloto herbs 434.6 mg/ kg, group 3: a combination of metformin 45 mg / kg BW with the extract of 434.6 mg/ kg (combination 1), and group 4: metformin 22.5 mg/ kg body weight with extract 434.6 mg/ kg (combination 2). Test animals are insulin resistant type 2 DM was made by administering 1.8 g fructose / kg body weight and fat diet for 50 days. Assay of glucose using a reagent kit. Observation of GLUT-4 expression in muscle cells by using immunohistochemical techniques. Insulin resistance rats was tested by using three parameters: (1) testing of blood glucose levels preprandial and postprandial (2) the hypoglycaemic activity of glibenclamide, and (3) observations of GLUT-4 protein expression in muscle tissue. Test results show that the animals had insulin resistant. Results, in this research antidiabetic activity assay indicate that the hypoglycaemic for combination 1 and combination 2 lower compared to a single administration of metformin or purified extract (p<0,05). From the above results concluded that the combination of sambiloto extract purified with metformin does not increase the potency of antidiabetic in single use.